Reconceptualising homophobia: by leaving 'those kids' alone. Issue 3 (3rd May 2020) - Allen, Louisa
ABSTRACT: 'How can we apprehend homophobia as more than we currently know?' This paper attempts a conceptual intervention to rethink current approaches to homophobia in schools. It draws on ideas from feminist philosopher Todd around attention and openness to uncertainty. It also employs queer theoretical notions of subjectless antihomophobia education from Airton, arguing there may be utility in understanding that homophobia is not held by a subject – as an attitude or set of meanings used against others. Interview narratives from a two-year research project exploring the production of sexual meanings at school offer a window into acknowledging homophobia as subjectless. That is, homophobia does not need a queer-identified subject to be its target to operate. Nor, does homophobia need an ignorant or fearful (human) subject to perpetuate it. Subjectless anti-homophobia education requires understanding homophobia as something in which all of us are implicated, and where homophobia is never ours alone.